Impact response of laminated glass with varying interlayer materials. (May 2020) - Zhang, Xiaowen; Liu, Haibao; Maharaj, Chris; Zheng, Mengyao; Mohagheghian, Iman; Zhang, Guanli; Yan, Yue; Dear, John P.
Highlights: This study investigates the influence of the interlayer materials on the low velocity impact performance of laminated glass. The effect of impact energy levels (3, 5, 10 and 15 J) has been explored on the impact resistance of laminated glass and the failure mechanisms have been assessed. The bullet points can be drawn as follows. The interlayer materials have a great influence on the impact performance of the laminated glass. The laminated glass with TPU or PVB interlayer exhibited better impact resistant properties than laminated glass with the TPU/SGP/TPU hybrid interlayer or the SGP interlayer when impacted at the lower 3 and 5 J impact energy levels, thought to be caused by the different modulus of the interlayer materials. The laminated glass with SGP or TPU/SGP/TPU hybrid interlayer showed better load carrying capacity and anti-deformation capability at the higher 10 and 15 J impact energy levels. This is because the mechanical properties of SGP at room temperature lead to a higher strength and a higher stiffness of the entire laminated glass structure. The ratios of the absorbed energy ( Ea ) to the incident energy ( Ei ) of the impactor for different laminated glass structures depend on the impact energies. The glass layers dominate the impact response of the laminated glass structures and lead to lower ea /ei values when subjected to the low energy impact e.g. 3 and 5 J. At the higher impact energy levels such as 10 and 15 J, the rebound of the impactor was affected by the viscoelasticity of the interlayers. Different rate-dependent properties of the SGP, TPU and PVB interlayers lead to the different values of ea /ei that are obtained for the studied laminated glass structures. Abstract: This study investigates the influence of the interlayer materials on the low velocity impact performance of laminated glass. By varying the impact velocity, with a drop-weight, the effect of impact energy levels (3, 5, 10 and 15 J) has been explored on the impact resistance of laminated glass and the failure mechanisms have been assessed. The four interlayer materials investigated were: SGP–Ionoplast as employed in Sentry Glas® Plus, TPU-Thermoplastic polyurethane, PVB-Polyvinyl butyral and a TPU/SGP/TPU hybrid interlayer. The drop weight method has been employed to obtain the energy dissipation, loading and deformation of the laminated glass. The low velocity impact results indicate that both the type of the interlayer materials and the impact energy have great influence on the impact performance of the laminated glass. The laminated glass with TPU and PVB interlayer exhibited better impact resistance than the laminated glass with SGP and TPU/SGP/TPU hybrid interlayer, when impacted at energies of 3 and 5 J (corresponding to impact velocities of 1.71 and 2.21 ms −1 respectively). However, the laminated glass with SGP and TPU/SGP/TPU hybrid interlayers has better load carrying capacity and better anti-deformation property than the TPU and PVB interlayers at the higher impact energies of 10 and 15 J (impact velocities of 3.13 and 3.83 ms −1 respectively). The results are thought to be attributed to the differences in the viscoelastic properties of the interlayer materials with strain rates.